Demographic Characteristics and History of Pulmonary TB Treatment in Malang City in 2022-2023 - Deniati, Ema Novita; Fauzia, Zalva Hanny; Imthiatiyyah, St. Mutrifatul; Haidar Rantaka, Muhammad Thoriq (citeus, 2025)
Tuberculosis (TB) is currently in thirteenth place as the main cause of death globally. In 2022, at East Java there were 78,799 cases of pulmonary TB. The success rate for TB treatment in East Java is 89.01 percent or has not yet reached the target for the Treatment Success Rate indicator in 2022, which is 90 percent. Meanwhile in Malang City, in 2022 there were 2,417 TB cases and this will increase in 2023 to 2,716 cases. The increase in cases occurs because people still think it's trivial, especially when they cough and are reluctant to get checked, but when the disease is serious, they just get checked. The goal of this research is to analyze the demographic characteristics and treatment history of pulmonary TB patients based on secondary data sourced from Malang City Health Office. The sample numbered 4,735 with a study design using descriptive methods using total population sampling techniques. The results showed that Sukun sub district have the highest number of pulmonary TB patients and most of pulmonary TB patients was 19 until 45 years old. In the gender variable, it was more common in men and in the employment status variable, there were more patients with working status. Treatment history was most frequently found in the new treatment category.